Navigating Complex Cardiovascular Pathologies: A Case Report on Aortic Arch Replacement in a Middle-Aged Male with Stanford A DeBakey I Aortic Dissection - Handari, Saskia Dyah; Firdaus, Muhammad; Sembiring, Yan Efrata (Heart Science Journal, 2024)
Background: Aorta dissection is characterized by the presence of an intimal tear, which permits the passage of blood through the tear and into the aorta media. This process leads to the separation of the intimal and the formation of a dissection flap, representing the true lumen and a newly formed false lumens. The incidence of aortic dissection varies between 0.2% and 0.8%. Management of acute aortic standford A aortic dissection primarily involves invasive surgical procedures.Case presentation: A middle-aged male patient, aged 40, who possesses risk factors including uncontrolled hypertension and obesity, arrived to the emergency room with symptoms of chest pain. He described the pain as tearing in nature and said that it radiated towards the abdominal. The examination findings included a blood pressure reading of 255/143, a widened mediastinum and cardiomegaly observed on the chest X-ray, a slight elevation in Hs-Troponin levels, and the presence of sinus rhythm with left ventricular hypertrophy. He underwent CT scan, which demonstrated the presence of an aortic dissection extending from the ascending to descending aorta, with no associated damage to the aortic valve from echocardiography. He was diagnosed with Standford A DeBakey I Aortic dissection and underwent preference replacement of the aortic arch and elephant trunk implantation instead of Bentall procedure.Conclusion: The surgical and perioperative methods employed may differ based on the specific clinical presentation and the nature of the aortic disease. Because there was no involvement of the aortic valve, we performed total aortic arch replacement and elephant trunk procedure over the Bentall procedure.